FREEDOM OF EXPRESSION AND DECRIMINALIZATION OF THE DEFAMATION IN THE REPUBLIC OF MACEDONIA - Majhosev, Andon; Mirkovski, Goran (Journal of process management and new technologies, 2017)
The freedom of expressionis one of the most important human civil and political rights which is guaranteed with many international and regional legal instruments established by UN, European Council, EU and etc. That is basic precondition for the development of one country. The freedom of expressionincluds not only the freedom to express one’s opinion or ideas but it also includes freedom to search information or ideas, receive informations or ideas and to pass the informations or ideas. In many countries in the world, as well in Macedonia, the freedom of expressionis not absolute but limited and the border is the respect of the freedom and the rights of other people, more specifically their reputation and honour. Reporters often deliberately or unintentionally, while doing their job, violate the right of freedom of speech by insulting or defaming others, most common public function holder (politicans). The politicans with their political power significantly influenced on the judicial organs so that they reach a verdict in their favor. Therefore the reporters were exposed to great pressure and very often they were punished by jail sentences. Setting the judical system this way it became limiting factor in the normal development of the reporters job. Until 2012 the insult and the defamation in Republic of Macedonian were considered criminal act and they were subjected to jail punishment. Since the law of civil liability for insult and defamation in 2012, the insult and the defamation don’t belong to corpus delicti that are in the sphere of the criminal right. Since then to this day the insult and the defamation are treated as violation.